Air Embolism during Upper Endoscopy: A Case Report - Yin Fang; Junbei Wu; Feng Wang; Lihong Cheng; Yunhong Lu; Xiaofei Cao (Korean Society of Gastrointestinal Endoscopy, 2019)
Air embolism is a rare complication of upper endoscopy and potentially causes life-threatening events. A 67-year-old man with a history of surgery of cardiac carcinoma and pancreatic neuroendocrine tumor underwent painless upper endoscopy because of tarry stools. During the procedure, air embolism developed, which caused decreased pulse oxygen saturation and delayed sedation recovery. He recovered with some weakness of the left upper limb in the intensive care unit without hyperbaric oxygen therapy. The etiology, clinical manifestations, and treatments of air embolism are discussed based on the literature reports. Although air embolism is uncommon in endoscopic examinations, the patients' outcomes could be improved if clinicians are alert to this potential complication, and promptly start proper diagnostic and therapeutic measures.